The Relationship Between Feeding Patterns and Stunting in Toddlers Aged 24-59 Months in the Working Area of the Gisting Community Health Center, Tanggamus Regency, Lampung - Azzahra, Luthfiana Fajrin; Firmansyah, Firmansyah (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Feeding patterns significantly influence stunting. Eating habits in children affect growth and development since food provides essential nutrients, vitamins, and minerals. Objective: To analyze the relationship between feeding patterns and stunting in toddlers in the Working Area of the Gisting Community Health Center, Tanggamus Regency, Lampung. Method: This was an analytical study with a cross-sectional design. Cluster random sampling was used, involving 82 mothers of toddlers as respondents. Data were collected using questionnaires and interviews. Feeding patterns were measured with the Child Feeding Questionnaire, while consumption patterns were assessed through a 24-hour recall. Stunting was identified using anthropometric measurements based on height-for-age and converted into z-scores. Results: Most toddlers had inappropriate feeding patterns (53.7%), while the majority were not stunted (62.2%). The chi-square test showed a significant relationship with p = 0.000. Conclusion: There is a significant association between feeding patterns and stunting in toddlers aged 24–59 months. Mothers should fulfill children’s nutritional needs by applying balanced and varied diets according to age requirements.